The results of research concerning preparations based on solution of Poltavian Bischofit conducted on broiler chickens - Бердник, В. П.; Бублик, О. О.; Бердник, І. Ю.; Щербак, В. І.; Марченко, Т. М.; Сугак, О. В. (Scientific Progress & Innovations, 2016)
The results of the study concern clinical and physiological parameters of 4 to 43 days old broilers' health state, who were given Poltavian Bischofit solutions along with food and water in 4 different solution versions. During the period, chickens had a satisfactory clinical condition. As an exception, there were three 14 to 20 days old chickens, who could not walk due to joint disease. One chicken recovered. Two 28 and 29 days old chickens died due to peritonitis and heat stroke, respectively. When comparing our broilers with the control research sample (6 females and 4 males), increased levels of hematopoesis and hemoglobin in the blood and average body-weight growth of 43 days old chickens were found in hens at 303.93 g (7 broilers) and roosters at 271.25 g (4 broilers) after the application of only one of four tested Bischofit solutions. This is the reason to recommend it for the test in farms, in 1 or 2 daily doses of magnesium-rich Bischofit as a supplement in the diet of broiler chickens.